2011
DOI: 10.1080/02500167.2011.589394
|View full text |Cite
|
Sign up to set email alerts
|

‘No ‘til we know.’Fela ba a tseba naa? Using African languages to communicate about HIV and AIDS to young South Africans

Abstract: An experiment was conducted in order to determine the extent to which the presentation of HIV and AIDS messages in different languages would affect the appreciation and comprehension of these messages among young South Africans. Interviews were carried out with 60 learners in rural and peri-rural schools in Limpopo Province. Four messages (on posters or in radio advertisements), were presented in three languages. The interviews focused on appreciation (to what extent do the participants like the messages?), pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Recent publications that discuss the findings of the project include Jansen and Janssen (2010), Lubinga and Jansen (2011), and Lubinga, Schulze, Jansen, and Maes (2010).…”
Section: Discussionmentioning
confidence: 97%
“…Recent publications that discuss the findings of the project include Jansen and Janssen (2010), Lubinga and Jansen (2011), and Lubinga, Schulze, Jansen, and Maes (2010).…”
Section: Discussionmentioning
confidence: 97%
“…We decided to choose a poster that scored relatively high on AC ( M = 2.36, SD = 1.09 on a scale of 1–4), and also relatively high on reported willingness to discuss it among peers ( M = 3.37, SD = 1.00, on a scale of 1–4). The poster was in English because the results of a previous study conducted on the comprehension of puzzling messages in two African languages and English indicated that there were no differences in comprehension by participants on the basis of the message languages (Lubinga & Jansen 2011 ). The poster included the verbal message, ‘If you care, do not share’, plus a combination of pictures: a couple hugging, a single flower with several bees hovering over it, and a red ribbon underneath it with the text, ‘Stop AIDS’.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaires were in English. The decision to use questionnaires in English follows a previous study in which interviews in two mother-tongue languages and English were used to find out the comprehension of puzzling HIV/AIDS messages (Lubinga & Jansen 2011 ). The results of that study did not indicate better comprehension, nor preferences among a similar group of learners for asking the questions in their mother-tongues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The language of the posters was English, following the results of a previous study on the effects of using African languages in HIV and AIDS messages (Lubinga and Jansen 2011). In this study, existing loveLife posters in two African languages and in English were presented to young Sepedi and Tshivenda mother-tongue speakers from Limpopo Province.…”
Section: Postersmentioning
confidence: 99%